Análisis multicriterio para elegir alternativas de solución al problema de desabastecimiento de agua potable en los municipios de Manaure y Uribia en el Departamento de la Guajira (2020)
One of the biggest problems worldwide is access to water supply sources, which not only affects the quality of life but also increases the inequality gap in the world, a situation that is no exception for Colombia. In this order of ideas, the department of La Guajira is determined as one of the departments most affected by the lack of this resource, given this situation the Constitutional Court issues Ruling T 302 of 2017, through which governmental entities are ordered to fully guarantee food, access to drinking water and health for all Wayuu children in the department of La Guajira. Therefore, this research proposes a concise proposal of alternatives that respond to the priority humanitarian situation of Alta Guajira, evaluating them under different criteria for their efficient choice to put them into practice. Initially, the water sources available in the department of La Guajira were considered, obtaining as surface sources: Ranchería River, Tapias River, Jeréz River, Cañas River, Ancho River; likewise, the subway water source is considered, and likewise, the inexhaustible water source that is the Caribbean Sea is considered. As a methodology, the Hierarchical Analytical Process was implemented, for which surveys were conducted to professionals and Wayuu indigenous leaders directly and/or indirectly related to the department's problems. Finally, after evaluating the alternatives, the best one contemplates as supply sources the Ancho River, Cañas River, Jeréz River, and Tapias River, considering a staggered catchment taking advantage of the water supply of each source depending on the time of the year, its distribution would be carried out through pipes and several distribution points or public basins, this alternative also contemplates supplying the capital of the department Riohacha.